Provocative testing of the esophagus and its future. Issue 1 (16th June 2016) - Farmer, Adam D.; Franchina, Marianna; Gregersen, Hans; Penagini, Roberto; Shaker, Anisa; Soffer, Edy
Abstract : Standard tests in clinical practice commonly fail to demonstrate a clear esophageal etiology for symptoms such as heartburn, dysphagia, or chest pain. Over the years, various provocative measures have been developed to provide a better understanding of the origins of such symptoms. Some measures, such as esophageal acid infusion or changing bolus consistency, can be easily incorporated into clinical practice. Others, such as multimodal stimulation systems, are more technically demanding. They have contributed to a better understanding of esophageal physiology in health and disease. Their role in clinical decision making is still evolving. This focused review provides a summary of the esophageal nociceptive pathways and how provocative testing can be used to interrogate their integrity.